"Let's Dance": A Dialogical Proposal for Analyzing Interactions and Positions in Couples Therapy. Issue 2 (3rd April 2021) - Cunha, Carla; Figueiredo, Catarina; Salgado, João
Abstract: The theory of the dialogical self, which is based upon the metaphor of the self as a dialogue between different voices and I-positions, conceptualizes the structure and functioning of the self as a product of communication and relational processes. The dynamics of the dialogical self imply an articulation between the individual self and the self in relationships with others. However, the theory of the dialogical self has seldom been applied to couples therapy. Therefore, in order to understand changes in relationships from a dialogical perspective, we decided to perform a case study for a couple, Victoria and Alfonso, evolving through four sessions of couples therapy. The Positioning Microanalysis method was applied to depict and characterize the self in relation to each half of the dyad in their continuous flow of positioning and repositioning, as characterized by their usual "dance" around a main theme developed throughout the sessions. The couples' problematic cycle (Victoria: I as rejected/not being cared for by him; Alfonso: I as rejecting/unable to express my support) was then reconfigured into an alternative, more adaptive cycle (Victoria: I as validating my needs and fighting my sensitivity to rejection; Alfonso: I as caring for her), through the emergence of an alternative position. This new position freed this couple and enabled them to innovate on the interactions that characterized their usual "dance".